The DNA and RNA sugar-phosphate backbone emerges as the key player. An overview of quantum-chemical, structural biology and simulation studies - Šponer, Jiří; Mládek, Arnošt; Šponer, Judit E; Svozil, Daniel; Zgarbová, Marie; Banáš, Pavel; Jurečka, Petr; Otyepka, Michal (Physical chemistry chemical physics, 2012)
Knowledge of geometrical and physico-chemical properties of the sugar-phosphate backbone substantially contributes to the comprehension of the structural dynamics, function and evolution of nucleic acids. We provide a side by side overview of structural biology/bioinformatics, quantum chemical and molecular mechanical/simulation studies of the nucleic acids backbone. We highlight main features, advantages and limitations of these techniques, with a special emphasis given to their synergy. The present status of the research is then illustrated by selected examples which include classification of DNA and RNA backbone families, benchmark structure-energy quantum chemical calculations, parameterization of the dihedral space of simulation force fields, incorporation of arsenate into DNA, sugar-phosphate backbone self-cleavage in small RNA enzymes, and intricate geometries of the backbone in recurrent RNA building blocks. Although not apparent from the current literature showing limited overlaps between the QM, simulation and bioinformatics studies of the nucleic acids backbone, there in fact should be a major cooperative interaction between these three approaches in studies of the sugar-phosphate backbone.
Keywords: molekulární struktura; DNA; Molecular Structure; Molecular Dynamics Simulation; Quantum Theory; sacharidy; simulace molekulární dynamiky; kvantová teorie; Carbohydrates; RNA; Phosphates; Computational Biology; fosfáty; výpočetní biologie